Ідеологічний чинник в історичній прозі для дітей (на матеріалі історичних повістей 20–30-х років ХХ століття) - Разживін, В.М. (Інститут літератури ім. Т.Г. Шевченка НАН України, 2009)
Статья посвящена исследованию исторической прозы. В ней рассмотрено влияние идеологического фактора на украинскую историческую повесть для детей 20 – 30-х годов ХХ века. Поставленная проблема рассмотрена на материале конкретных художественных произведений. Анализируемые повести Г. Бабенко и И. Крипякевича позволяют показать процесс корреляции авторами исторического материала в зависимости от политических убеждений, что подтверждает наличие идеологического влияния на их творчество. The article is devoted to the study of historical story. It discloses the influence of the ideological factor of the historical сhildren story of the 20-th – 30-th years in the XX-century. Appropriateness of such formulation of the problem is proved on the basis of the material of actual fiction. The reviewed narratives by G. Babenko and I. Krypjakevych enable us to show the process of the authors’ correlation of historical material depending on political beliefs; and in the turn it confirms the existence of ideological influence on their works.